Technical considerations for generating somatosensation via cortical stimulation in a closed-loop sensory/motor brain-computer interface system in humans. (May 2019) - Kramer, Daniel R.; Kellis, Spencer; Barbaro, Michael; Salas, Michelle Armenta; Nune, George; Liu, Charles Y.; Andersen, Richard A.; Lee, Brian
Highlights: Comparison of electrode array modalities for somatosensory BCI in humans. Microelectrode array has good resolution, but poor coverage and high redundancy. 3 cm electrocorticography spacing has ideal balance of coverage, and specificity. Abstract: Somatosensory feedback is the next step in brain computer interface (BCI). Here, we compare three cortical stimulating array modalities for generating somatosensory percepts in BCI. We compared human subjects with either a 64-channel "mini"-electrocorticography grid (mECoG; 1.2-mm diameter exposed contacts with 3-mm spacing, N = 1) over the hand area of primary somatosensory cortex (S1), or a standard grid (sECoG; 1.5-mm diameter exposed contacts with 1-cm spacing, N = 1), to generate artificial somatosensation through direct electrical cortical stimulation. Finally, we reference data in the literature from a patient implanted with microelectrode arrays (MEA) placed in the S1 hand area. We compare stimulation results to assess coverage and specificity of the artificial percepts in the hand. Using the mECoG array, hand mapping revealed coverage of 41.7% of the hand area versus 100% for the sECoG array, and 18.8% for the MEA. On average, stimulation of a single electrode corresponded to sensation reported in 4.42 boxes (range 1–11 boxes) for the mECoG array, 19.11 boxes (range 4–48 boxes) for the sECoG grid, and 2.3 boxes (range 1–5 boxes) for the MEA. Sensation in any box, on average, corresponded to stimulation from 2.65 electrodes (range 1–5 electrodes) for the mECoG grid, 3.58 electrodes for the sECoG grid (range 2–4 electrodes), and 11.22 electrodes (range 2–17 electrodes) for the MEA. Based on these findings, we conclude that mECoG grids provide an excellent balance between spatial cortical coverage of the hand area of S1 and high-density resolution.